Colistin nephrotoxicity increases with age. (October 2014) - Balkan, Ilker Inanc; Dogan, Mustafa; Durdu, Bulent; Batirel, Ayse; Hakyemez, Ismail N.; Cetin, Birsen; Karabay, Oguz; Gonen, Ibak; Ozkan, Ahmet Selim; Uzun, Sami; Demirkol, Muhammed Emin; Akbas, Sedat; et al.
Abstract Background: Colistin (COL) has become the backbone of the treatment of infections due to extensively drug-resistant (XDR) Gram-negative bacteria. The most common restriction to its use is acute kidney injury (AKI). Methods: We conducted a retrospective cohort study to evaluate risk factors for new-onset AKI in patients receiving COL. The cohort consisted of 198 adults admitted to 9 referral hospitals between January 2010 and October 2012 and treated with intravenous COL for ≥ 72 h. Patients with no pre-existing kidney dysfunction were compared in terms of risk factors and outcomes of AKI graded according to the RIFLE criteria. Logistic regression analysis was used to identify associated risk factors. Results: A total of 198 patients met the inclusion criteria, of whom 167 had no pre-existing kidney dysfunction; the mean patient age was 58.77 (± 18.98) y. Bloodstream infections (34.8%) and ventilator-associated pneumonia (32.3%) were the 2 most common indications for COL use. New-onset AKI developed in 46.1% of the patients, graded as risk (10%), injury (15%), and failure (21%). Patients with high Charlson co-morbidity index (CCI) scores (p = 0.001) and comparatively low initial glomerular filtration rate (GFR) estimations (p < 0.001) were more likely to develop AKI, but older age (p = 0.001; odds ratio 5.199, 95% confidence interval 2.684–10.072) was the major predictor in the multivariate analysis. In-hospital recovery from AKI occurred in 58.1%, within a median of 7 days. Conclusions: COL-induced nephrotoxicity occurred significantly more often in patients older than 60 y of age and was related to low initial GFR estimations and high CCI scores, which were basically determined by age.